THE INFLUENCE OF POWER PRESTIGE, ANXIETY, DISTRUST AND CREDIT CARD USAGE ON COMPULSIVE BUYING - Daun, Stella C.; Pangemanan, Sifrid S.; Mekel, Peggy A. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Consumer behavior has been a topic of interest for many academics in the past few years, and one of the many subjects from consumer behavior is compulsive buying. Compulsive buying has known as an abnormal form of consumer behavior, regarded as the dark side of consumption. The purpose of this study is to analysis the influence of power prestige, anxiety, distrust, and credit card usage on compulsive buying of college student. The population observed was IBA students who use credit card with sample as many as 100 respondents. This research used quantitative analyze by using questionnaires and used multiple regression analysis. Result showed that power prestige, anxiety, distrust, and credit card usage influence compulsive buying simultaneously but not partially because distrust variable has no significant influences to compulsive buying. However, measuring money attitudes gives a clearer picture of how students perceive money and how money makes them feel towards themselves and towards various products or services. Therefore, further studies should widen the variable of money attitude that can potentially influence compulsive buying. A factor which captures obsession with money would be an improvement. It is captured by the power prestige dimension, but could be made explicit as a separate factor. Keywords: compulsive buying, power prestige, anxiety, distrust, credit card